Attitudes towards and experiences with sourdough and baker’s yeast bread amongst participants in a randomised controlled trial: a qualitative study - Lisa Garnweidner-Holme; Marit Hallquist; Solveig Ivara Watters; Mia Gjøvik; Marius Pihl Frederiksen; Stephanie Jonassen; Ina Ravnanger; Christine Henriksen; Mari C.W. Myhrstad; Vibeke H. Telle-Hansen (Food & Nutrition Research, 2022)
Background: Bread is an important source of dietary fibre. However, an increasing number of individuals exclude bread from their habitual diet for various reasons. In recent years, sourdough bread has increased in popularity, and clinical studies have indicated that sourdough bread may decrease gastrointestinal symptoms. Objective: To investigate attitudes towards and experiences with sourdough and baker’s yeast bread amongst participants in a randomised controlled trial (RCT), the health effects and consumer aspects of bread (HELFAB) study. Design: We conducted individual interviews with 10 participants who stated to be sceptical about bread and who participated in an RCT to investigate the health effects of sourdough bread versus baker’s yeast bread. The participants were interviewed on two occasions (before and after the RCT). Interviews were conducted digitally between September and December 2020 and were thematically analysed. Results: Half of the interviewed participants experienced gastrointestinal symptoms, such as pain in the stomach, when they consumed bread prior to the RCT. They often preferred sourdough bread to baker’s yeast bread both before and after the study, since they found that sourdough bread was easier to digest. Participants who were sceptical about bread prior to the study became more positive about bread because of their experiences with the intervention breads. This finding was mainly related to the taste and consistency of sourdough bread. The participants often associated bread with healthiness, mainly due to the dietary fibre content in bread. Conclusions: Sourdough bread with increased dietary fibre may be an important source of dietary fibre for those who perceive gastrointestinal problems from baker’s yeast bread. Participants in this qualitative study stated to change their attitudes towards bread, mainly due to perceived healthiness of the intervention bread.